(untitled) (Research, Society and Development, 2022)
Objective: To report the experience of clinical pharmacists in the development and application of an instrument for pharmacotherapeutic follow-up based on the FAST HUG MAINDENS mnemonic in a COVID-19 intensive care unit. Methodology: The elaboration of the instrument was carried out by consulting works that used the mnemonic in the construction of their tools, as well as in the needs observed in the experience of the service. Results: Data collection was performed daily through analysis of the patient’s electronic medical record, as well as during patient visits, where instruments related to patients and records of other professionals were observed. Once drug-related problems were identified, the intervention was carried out with the responsible professional, and every action performed by the pharmacists was recorded in the patient’s electronic medical record. The follow-up form allowed the pharmacist to monitor fundamental aspects in the care of critically ill patients with COVID-19. Conclusion: The elaboration and use of the pharmacotherapeutic follow-up instrument allowed the standardization of the clinical pharmacy service for critical patients with COVID-19, facilitating the identification of more points of pharmaceutical intervention and streamlining the pharmacist’s performance after the identification of drug-related problems.